Strategi UMKM di Alun – Alun Kidul Yogyakarta untuk Meningkatkan Kualitas Layanan dan Produk Penjualan - Mutiara Agus Wahyuni; Hurian Kamela (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The aim of this research is to analyze MSME strategies related to customer satisfaction with quality services and products. This study applies a quantitative approach. Fifty respondents from the MSME consumer population who buy food and drinks in the southern Alun - Alun area were involved in this research. The results show that better product service can increase customer satisfaction.